The effect of renin-angiotensin-system inhibition on survival and recurrence of N3+breast cancer patients - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2015)
Purpose: The purpose of this study was to evaluate the association between the rennin-angiotensin system (RAS) inhibition and the risk of breast cancer (BC) recurrence and progression in N3 positive patients. Methods: The medical records of patients treated for N3 positive BC in Hacettepe Cancer Institute between 2005 and 2012 were evaluated. Angiotensin converting enzyme (ACE) inhibitors/angiotensin receptor blockers (ARB) users were defined as patients who took these medications for at least 6 months in no evidence of disease (NED) stage after the initial diagnosis. The primary and secondary outcome was disease-free survival (DFS) and overall survival (OS). Kaplan-Meier and Cox proportional hazard models were used. Results: A total of 218 pathologic N3 BC patients were included. Follow up ranged from 12 to 212 months (median 49.58). Thirty one patients used ACE inhibitors/ARBs. Univari ate analysis showed BC recurrence was lower and OS was higher among patients who used ACE inhibitors/ ARBs, however without reaching statistical significance (p=0.38 and p=0.24, respectively). RAS inhibition was associated with reduced risk of pathologic N3 BC recurrence. Conclusion: To the best of our knowledge this is the second study showing that the use of ACE inhibitors/ARBs may be effective in N3 BC. Because of the limited therapeutic options in BC, new drugs or new therapeutic modalities should be considered. In the future, studies with long-term follow-up may be helpful for their implication in clinical practice.
Keywords: breast cancer; N3 positive; RAS inhibition; recurrence; survival; BREAST-CANCER; ACE-INHIBITORS; TYPE-1 RECEPTOR; RISK; GROWTH; ANGIOGENESIS; METAANALYSIS; CARCINOMA